Cooperative effects on the compaction of DNA fragments by the nucleoid protein H-NS and the crowding agent PEG probed by Magnetic Tweezers - Cristofalo, M.; Marrano, C.A.; Salerno, D.; Corti, R.; Cassina, V.; Mammola, A.; Gherardi, M.; Sclavi, B.; Cosentino Lagomarsino, M.; Mantegazza, F. (Biochimica et biophysica acta. General subjects, 2020)
DNA bridging promoted by the H-NS protein, combined with the compaction induced by cellular crowding, plays a major role in the structuring of the E. coli genome. However, only few studies consider the effects of the physical interplay of these two factors in a controlled environment. We apply a single molecule technique (Magnetic Tweezers) to study the nanomechanics of compaction and folding kinetics of a 6 kb DNA fragment, induced by H-NS bridging and/or PEG crowding. In the presence of H-NS alone, the DNA shows a step-wise collapse driven by the formation of multiple bridges, and little variations in the H-NS concentration-dependent unfolding force. Conversely, the DNA collapse force observed with PEG was highly dependent on the volume fraction of the crowding agent. The two limit cases were interpreted considering the models of loop formation in a pulled chain and pulling of an equilibrium globule respectively. We observed an evident cooperative effect between H-NS activity and the depletion of forces induced by PEG. Our data suggest a double role for H-NS in enhancing compaction while forming specific loops, which could be crucial in vivo for defining specific mesoscale domains in chromosomal regions in response to environmental changes. •In the presence of H-NS alone, the DNA displays a step-wise collapse due to the formation of multiple bridges.•In presence of PEG alone, the DNA collapses at a force highly dependent on the volume fraction of the crowding agent.•The combination of the two agents displays a cooperative effect, i.e. cellular crowding influences H-NS activity.